Evaluation of the response of different tomato genotypes to Fusarium oxysporum breed 3 - Gayosso, Odilon; Chávez-Aguilar, Griselda; López-Benítez, Alfonso; Marroquín-Morales, José Ángel; Lpéz-Aguilar, Kelvin; Hidalgo-Ramos, Dreyli Maygualida (Revista Mexicana de Ciencias Agrícolas, 2021)
One of the phytosanitary problems limiting the production of tomato crop (Solanum licopersicum L.) worldwide and nationally is vascular wilt caused by Fusarium oxysporum f. sp. lycopersici (Fol), causing large economic losses. The objective of this study was to determine the variability in virulence of Fusarium strains isolated from tomato plants with typical symptoms of vascular wilt in tomato-producing plots in Hidalgo state and to assess the incidence and severity of Fol breed 3 in seven tomato genotypes. For the identification of breeds pathogenicity tests were performed on differential materials, in addition a disease index was used to calculate the area under the disease progress curve (ABCPE), which allowed to identify genotypes with tolerance to Fol. Fol breeds 2 and 3 were identified in a ratio of 33 and 67%, respectively, in addition information is provided about behavior of seven tomato genotypes, of which Y53 and D3 had the lowest incidence of Fol, highlighting the importance of being used in future work on resistance to this pathogen.